Is Sedentary Behavior Associated With Executive Function in Children and Adolescents? A Systematic Review - Li, Shiyuan; Guo, Jinyang; Zheng, Kefeng; Shi, Mengyao; Huang, Tao (Frontiers in Public Health, 2022)
Background: Prolonged time on sedentary behavior, especially screen-based sitting time, is associated with unfavorable health indicators in children and adolescents. However, the effects of sedentary behaviors on cognitive function remain to be elucidated. Objective: The purpose of this systematic review was to synthesize the evidence on the associations of sedentary behavior with executive function in children and adolescents. Methods: Four electronic databases (i.e. PubMed, Web of Science, PsycINFO, and SPORTDiscus) were searched for studies examining the associations between sedentary behavior and executive function in children and adolescents. Study quality was assessed by the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: A total of 1151 records were initially identified through database searches and other searches. Twelve cross-sectional and four longitudinal studies met the inclusion criteria. Of the 16 studies, six studies found significant negative associations between sedentary behavior and executive function, and two studies presented positive associations. Eight studies measured sedentary time using accelerometers and showed varied associations between objectively measured sedentary time and executive function. Nine studies measured screen-based sedentary behavior, of which five studies found negative associations of sedentary time with executive function. Conclusion: The available evidence on the associations between sedentary behavior and executive function is not conclusive in children and adolescents. However, screen-based sedentary behavior may be negatively associated with executive function.